THE TYPE OF COOPERATIVE LEARNING EVERYONE IS A TEACHER AND IMAGE MEDIA AT STRUCTURE MATERIAL AND PLANT NET WORK CLASS VIII J ODD SEMESTER 2018/2019 IN MIDLE SCHOOL 1 KARANGTANJUNG - Wiwin Pertiwi (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2019)
ABSTRACTThe low reading interest, motivation, and student learning readiness in school are some of the factors that cause the process of learning to be hampered and the difficulty of these students in mastering the material, especially the structure and function of plants. This is intended by 78% of class VIII J students who have not achieved the minimum completeness criteria. The purpose of this Classroom Action Research (CAR) is to increase student learning outcomes in the material structure and function of plants through cooperative learning, everyone is a teacher here and the use of media images. In this study PTK was conducted in 2 cycles and the instruments used were multiple choice tests and student questionnaires. The results of the study showed that cooperative learning for everyone is a teacher here and the media image can improve students' cognitive learning outcomes by 12.37%. The results of the learning questionnaire showed satisfactory results because some students gave a positive response to the application of learning with everyone is a teacher here and media images. Keywords: Learning Outcomes, everyone is a teacher here, picture media, structure and function of plant tissue, and Classroom Action Research